Quality enhancement and review process (Council on Quality and Leaderships in Supports for People with Disabilites, 1998)
'The Council conducts its international quality enhancement work through the development of standards of quality; development and dissemination of materials; the provision of training, consultation and technical assistance; and the operation of an accreditation program. The Council conducts its quality enhancement work both directly and through collaborative agreements and partnerships with other organisations, systems and coalitions, both public and private.'